ESTIMACIÓN DE COSTOS DE INVERSIÓN PARA UN ESTUDIO DE CASO: DREN TOPO Y DREN CON TUBERÍA EN LA REGIÓN CENTRAL SANTAFESINA - CAMUSSI, G. (Universidad Nacional del Litoral, 2019)
The period 1970- 2018 is described, in a part of the Pampas region of Argentina, by the occurrence of extreme events with a predominance of water excesses. These problems can be mitigated through the application of integrated management techniques. The aim of this work was to estimate, applying the methodology of the case study, the costs of the investments necessary to implement water management techniques: the storm drain and pipe drain. The results obtained was expressed in August 2.018 currency. The investment value for the mole drainage was $/ha 9.268 and for the drain with pipe $/ha 48.464. The NPV was of $ 106.319 and of $ 433.348 for the alternative mole drainage and drain with pipe respectively. It is necessary to collect information corresponding to the impact of both techniques to be able to evaluate these projects with respect to other viable alternatives from the technical and economic point of view.